2016
DOI: 10.1302/2046-3758.511.2000495
|View full text |Cite
|
Sign up to set email alerts
|

Is the hip capsule thicker in diseased hips?

Abstract: ObjectivesThe purpose of this study was to compare the thickness of the hip capsule in patients with surgical hip disease, either with cam-femoroacetabular impingement (FAI) or non-FAI hip pathology, with that of asymptomatic control hips.MethodsA total of 56 hips in 55 patients underwent a 3Tesla MRI of the hip. These included 40 patients with 41 hips with arthroscopically proven hip disease (16 with cam-FAI; nine men, seven women; mean age 39 years, 22 to 58) and 25 with non-FAI chondrolabral pathology (four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…7,10,52,54,65 All lateral iliofemoral ligaments were also relatively thick, as measured after the capsulotomy. This finding coincided with previous imaging studies that found thicker anterosuperior capsules in symptomatic cam FAI 63,80 and suggested that our cohort was representative of individuals at risk of symptoms. Fourth, we performed the T-capsulotomy instead of an interportal-only capsulotomy.…”
Section: Discussionsupporting
confidence: 92%
“…7,10,52,54,65 All lateral iliofemoral ligaments were also relatively thick, as measured after the capsulotomy. This finding coincided with previous imaging studies that found thicker anterosuperior capsules in symptomatic cam FAI 63,80 and suggested that our cohort was representative of individuals at risk of symptoms. Fourth, we performed the T-capsulotomy instead of an interportal-only capsulotomy.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to mechanical responses, tissue dimensions of capsular ligaments (i.e., thickness and length) can also adapt with progressive arthritis, which can further result in larger cross-sectional areas and tighter capsular ligaments [37][38][39] . Since the previous material characteristics were from excised capsules of cadaveric hips without pathology, more imaging modalities evolved to quantify the capsular thickness of hips with pathology using magnetic resonance imaging (MRI) [38][39][40] . Anatomy of the capsular ligaments illustrated with a left-sided hip model in neutral position ( Fig.…”
Section: Propertiesmentioning
confidence: 99%
“…In terms of functional stability, it further suggests that the aperture mechanism of the zona orbicularis concentrically gathers these posterior thin fibers to create the stability-inducing collar during extreme hip motions. More recently, the MRI study by Rakhra et al further compared 3 groups: hips with cam FAI, hips with chondrolabral pathology, and healthy control hips 38 . They indicated that the capsule thickness of the cam FAI group was similar to the chondrolabral pathology group.…”
Section: Propertiesmentioning
confidence: 99%
See 2 more Smart Citations